Recovery from training: a brief review - Bishop, P. A.; Jones, E.; Woods, A. K. (The Journal of Strength and Conditioning Research, 2008)
Athletes spend a much greater proportion of their time recovering than they do in training. Yet, much attention has been given to training with very little investigation of recovery. The purpose of this review is to stimulate further research into this vital area of training. Recovery can be categorized in three terms: i) immediate recovery between exertions; ii) short-term recovery between repeats (e.g., between resistance sets or interval bouts); and iii) training recovery between workouts. The focus of this review is training recovery. Full training recovery is essential to optimal performance and improvement. This review includes an examination of extant research on recovery and a very brief review of some potential modalities and techniques for hastening recovery and the time course of recovery and responses to some treatments. Measures of recovery and practical considerations are discussed briefly. Much research is needed in this area, but there are obstacles to high quality research. Attention must be given to key issues in research on recovery, especially the individual response to recovery treatments.